Just another day in the life of Hopalong Cassidy. Issue 1 (1st March 2017) - Groves, Derham
The American actor William Boyd (1895–1972) was world famous for his portrayal of Clarence E. Mulford's fictional cowboy Hopalong Cassidy via comics, films, radio and television. In November 1954, Boyd travelled to Australia (Darwin, Melbourne, Adelaide, and Sydney) for sixteen hectic days to raise money for disabled children. 'Just another day in the life of Hopalong Cassidy' focuses on Friday, 12 November 1954, one of the four days that Boyd spent in Melbourne. Somewhat in the manner of French writer Georges Perec (Perec [1978] 2009), it documents Boyd's activities on that very busy day – including his visits to the Royal Children's Hospital, Yooralla, the Victorian School for Deaf Children, and Wirth's Circus – from the points of view of Boyd himself and several people who either saw or met their cowboy hero on the 12th. In the process of re-telling their stories, a unique picture of everyday life in Melbourne in 1954 emerges.